Establishment of Islamic Banking System in Afghanistan: Factors Have Led to the Late Establishment of Islamic Banking - Salim, Mohammad Salim (Hikmatuna : Journal for Integrative Islamic Studies, 2020)
This article aims to find the factors causing the underdevelopment of Islamic banking in Afghanistan. The method used is qualitative with a sociology of religion approach and is included in the category of policy research. The results of this study indicate that almost all of Afghanistan's population is Muslim and 90% of Afghans refuse the establishment of conventional banks on the grounds of interest. As for the causes of the delay in Islamic banking in Afghanistan, namely: First, political instability. Second, the economy is weak. Third, lack of legislative support. Fourth, support from scholars. Fifth, lack of public information. Sixth, the lack of experts in their fields.